2010
DOI: 10.1371/journal.pone.0013251
|View full text |Cite
|
Sign up to set email alerts
|

Treating Viral Exacerbations of Chronic Obstructive Pulmonary Disease: Insights from a Mouse Model of Cigarette Smoke and H1N1 Influenza Infection

Abstract: BackgroundChronic obstructive pulmonary disease is a progressive lung disease that is punctuated by periods of exacerbations (worsening of symptoms) that are attributable to viral infections. While rhinoviruses are most commonly isolated viruses during episodes of exacerbation, influenza viruses have the potential to become even more problematic with the increased likelihood of an epidemic.Methodology and Principal FindingsThis study examined the impact of current and potential pharmacological targets namely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 41 publications
12
80
0
Order By: Relevance
“…Inflammation in COPD is driven by a variety of stimuli, including oxidative stress, cytokines and tolllike receptor (TLR) stimulation by bacteria and viruses. Previous animal model data [10,31] and the current results therefore show evidence of efficacy for PPAR-c agonists in the prevention of inflammation caused by oxidative stress and/or TLR stimulation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Inflammation in COPD is driven by a variety of stimuli, including oxidative stress, cytokines and tolllike receptor (TLR) stimulation by bacteria and viruses. Previous animal model data [10,31] and the current results therefore show evidence of efficacy for PPAR-c agonists in the prevention of inflammation caused by oxidative stress and/or TLR stimulation.…”
Section: Discussionsupporting
confidence: 73%
“…Rosiglitazone inhibits LPS-induced airway neutrophilia in an animal model [10], and here we show that rosiglitazone inhibits cigarette smoke-induced pulmonary neutrophilia in an animal model. H1N1 infection after 4 days of cigarette smoke exposure causes corticosteroid-resistant pulmonary inflammation in mice that is attenuated by pioglitazone [31]. This model of infection coupled with cigarette smoke-induced inflammation can be argued to resemble exacerbations of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the mechanism of these augmented inflammatory and remodeling responses is mediated by the MAVS/PKR/IL-18R␣/interferon (IFN)-␥ pathway. Several other studies (16,48) also confirm this enhanced inflammatory response in a CS-induced COPD mouse model. Although innate immunity plays an important role in COPD exacerbation-, CS-or virus-induced inflammatory and remodeling responses, the mechanisms that mediate these responses have not been completely defined.…”
Section: Effects Of Cs In Animal Modelssupporting
confidence: 56%
“…The demographic variables that could affect the distribution of influenza A infections in populations are gender [16][17][18][19], age [15], clinical signs [20], vaccination against flu [21], usage of antimicrobials [22,24], smoking habits [25,29], and ethnicity [30,31].…”
Section: Introductionmentioning
confidence: 99%